Internal Whistleblowing and Perceptions of Organizational Politics, Pressure, and Professional Commitment - Risty, Ilyona; Aprilia Beta Suandi; Alif, Muhammad Ikhsan (Journal of Indonesian Economy and Business, 2025)
Introduction/Main Objectives: This study examines the influence of organizational political perceptions of internal whistleblowing intention, specifically investigating the role of professional commitment on the pressure felt by employees within the framework of the conservation of resources theory. Background Problems: Previous research has focused on what factors can increase internal whistleblowing intention, while there are contextual factors that cannot be ignored, specifically the state of the working environment that may hinder such intention. Novelty: This research investigates a different phenomenon from the point of view of an environment that creates a negative perception while also linking it to the professional commitment to the impact of internal whistleblowing intentions. Research Methods: This study employs a questionnaire-based survey method targeting employees of banks affiliated with the Association of Stated-Owned Banks in Indonesia. The sample consists of 115 participants and the data were analyzed using structural equation modeling (SEM). Findings/Results: The findings of this research suggest that employees' views on organizational politics and the corresponding pressure hinder their willingness to report violations. Nevertheless, a strong level of professional dedication does not lessen the impact of organizational politics on perceived pressure. This underscores the necessity for organizations to cultivate a cooperative atmosphere that can diminish the adverse perceptions of organizational politics. Conclusion: This research carries particular importance, notably within the financial industry, illustrating how the interactions among organizational politics, pressure, and professional commitment influence employees' tendency toward internal reporting of misconduct. Further, this research enriches the discourse on internal whistleblowing, providing a richer conceptualization of its determinants from both environmental and situational perspectives.